The Influence of Brand Image and Excellent Service on Consumer Loyalty at CV. Belilas Motorindo Mandiri in Selensen (Indragiri Hilir) - Risem Candina; Mashur Fadli; Mandataris (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research was proposed to understand the influence between brand image and excellent service on CV. Belilas Motorindo Mandiri in Selensen (Indragiri Hilir). Rapid changes in the industrial sector have resulted in many products entering the market. Every consumer has different attitudes and behavior towards a product. Companies must be able to create innovative policies and strategies to gain the trust and loyalty of consumers which is very important. The independent variables are brand image and excellent service, while the dependent variable is consumer loyalty. The method used in this research is quantitative. The sample used was purposive sampling of CV consumers. Belilas Motorindo Mandiri Selensen. The data source used in this research is primary data obtained by distributing questionnaires, then processed using SPSS software. The results of the research prove that the variables brand image and service excellence simultaneously have a significant influence on consumer loyalty.